2022
DOI: 10.46843/jiecr.v3i2.99
|View full text |Cite
|
Sign up to set email alerts
|

Zoom Utilization as an Online Learning Media during the COVID-19 Pandemic

Abstract: This research aims to analyze teachers’ digital literacy in the learning process at public elementary schools in Bengkulu, Indonesia. The focus is on teachers’ use of technological devices, especially their proficiency in operating, designing learning media, and utilizing digital media as a learning tool. This study employed qualitative research approach with descriptive type. The subjects were determined based on purposive with education background as the inclusive criteria. The data was collected using inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Likewise, a previous study conducted by Mittelmeier et al (2019) concluded that one of the most important things about distance learning is access to good technology, which has a positive impact on students' academic adjustment. Zainal et al (2022) also suggest that an unstable internet connection might cause students to not be able to hear and understand the learning process clearly. From the explanation above, it can be concluded that some of the difficulties expressed by the informants are in the realm of the teachers' pedagogic competence, such as difficulties in compiling or designing lesson plans, determining appropriate distance learning methods, and managing learning that can affect the earning activities of students.…”
Section: Response To Government Policy Regarding Distance Learningmentioning
confidence: 99%
“…Likewise, a previous study conducted by Mittelmeier et al (2019) concluded that one of the most important things about distance learning is access to good technology, which has a positive impact on students' academic adjustment. Zainal et al (2022) also suggest that an unstable internet connection might cause students to not be able to hear and understand the learning process clearly. From the explanation above, it can be concluded that some of the difficulties expressed by the informants are in the realm of the teachers' pedagogic competence, such as difficulties in compiling or designing lesson plans, determining appropriate distance learning methods, and managing learning that can affect the earning activities of students.…”
Section: Response To Government Policy Regarding Distance Learningmentioning
confidence: 99%
“…solution for achieving student learning outcomes in the era of society 4.0 (Argaheni, 2020;Zainal et al, 2022). In many studies, it has been mentioned that the achievement of the learning process assisted by digital technology can improve student skills (Izhar et al, 2022).…”
mentioning
confidence: 99%